GROWTH, LEAF WATER POTENTIAL, PHOTOSYNTHETIC PIGMENTS, COMPATIBLE SOLUTES AND YIELD COMPONENTS IN COWPEA LANDRACES UNDER SALINITY - Nabi Fahima; Şadji-Ait Kaci Hamida; Chebaani Meriem; Chaker Haddadj Assia; Ounane Sidi Mohamed (Natural Resources and Sustainable Development)
Soil salinity is a major constraint to food production because it limits crop yield. In this study, effect of applied NaCl on growth, proline, sugar content, leaf water potential, photosynthetic pigment concentrations and components of yield of five cowpea plant (Vigna unguiculata L. Walp) P1, P7, P13, P17 and P23was investigated. The experiment was carried out in pots under glasshouse at École Nationale Supérieure Agronomique, Algeria during 2023. The soil used was irrigated with NaCl and the rates of 1.93, 3.8, 4.7 and 6.0. dS m-1 NaCl. Salt stress was started 20 days after the start of the experiment and during 2 months. Growth (height, number of leaves and leaf area) and yield (number of pods / plant, length of pods / plant, weight of 100 seeds and number of seeds / pods) of the cowpea plants was inhibited by salinity. Application of NaCl significantly decreased leaf water potential, photosynthetic pigment (such as chlorophyll a, chlorophyll b, total chlorophyll and carotenoid). However, it could stimulate traits that could lead to the survival of cowpea plant in saline environment due to proline and sugar accumulations that increased as a result of salt stress. However, the effects vary depending on the level of salt and the population concerned. P1, P7 and P17 were less affected by salt than the sensitive cultivars P13 and P17.Our results suggests that the NaCl tolerance of this cultivars is supported by better yield, the less pigment and leaf water potential and a higher osmotic adjustment.